2017
DOI: 10.1111/rda.13017
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of immobilized cryopreserved bovine semen used for timed artificial insemination

Abstract: The SpermVital technology comprises embedding of spermatozoa within an alginate gel to facilitate release of sperm cells over a prolonged period in utero after AI. The aim of this study was to examine whether the survival time of spermatozoa is extended when applying this immobilization technology in combination with cryopreservation. Sperm cell survival (acrosome and plasma membrane integrity) was studied in vitro for 48 hr at physiological temperature. One dose of SpermVital (SV) semen was compared with sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Moreover, reduction in levels of AIL spermatozoa of both C and SV semen over time was lower than for B semen. Recently, comparable fertility rates were achieved after early AI with semen processed by the SpermVital ® technology in comparison with double AI with B semen (Alm‐Kristiansen et al., ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, reduction in levels of AIL spermatozoa of both C and SV semen over time was lower than for B semen. Recently, comparable fertility rates were achieved after early AI with semen processed by the SpermVital ® technology in comparison with double AI with B semen (Alm‐Kristiansen et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Although the first commercialized production line of SpermVital ® semen has shown decreased post-thaw sperm quality compared to conventionally processed semen, an equal fertility rate was achieved for the two semen types (Standerholen et al, 2015). Furthermore, early insemination with SpermVital ® was comparable with double insemination of conventionally processed semen (Alm-Kristiansen et al, 2017). The SpermVital ® technology was commercialized in 2010 and is continuously under development to meet the demands in the AI markets.…”
Section: Introductionmentioning
confidence: 99%
“…The other aliquot was diluted in a two‐step dilution procedure in Biladyl ® (hereafter referred to as B) extender (13,500/0,004–0,006, Minitube GmbH, Tiefenbach, Germany) to a final standard concentration of 15 million per straw. All processed semen samples were cryopreserved as described by Alm‐Kristiansen et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in an attempt to prolong spermatozoa lifespan in vivo in the female, new semen processing methods have been established. Bovine sperm cells can be encapsulated in alginate beads (Perteghella et al, ) or immobilized by the SpermVital ® technology in solid alginate gel before freezing (Alm‐Kristiansen et al, ; Standerholen et al, ). Common goal for all processing methods is to minimize sperm cryo‐injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Timing of AI relative to oestrous signs is assumed more flexible applying SV semen compared with standard semen. Alm‐Kristiansen et al () reported similar pregnancy rates between AIs using a single AI dose with immobilized SV semen early in heat and AIs using standard processed semen inseminated on two consecutive days. Further, in vitro evaluation of SV spermatozoa quality post‐thaw and following incubation has demonstrated prolonged viability compared with standard processed semen (Alm‐Kristiansen et al, ).…”
Section: Introductionmentioning
confidence: 93%